Cognitive Illusions of Authorship Reveal Hierarchical Error Detection in Skilled Typists - Logan, Gordon D; Crump, Matthew J.C (Science (American Association for the Advancement of Science), 2010)
The ability to detect errors is an essential component of cognitive control. Studies of error detection in humans typically use simple tasks and propose single-process theories of detection. We examined error detection by skilled typists and found illusions of authorship that provide evidence for two error-detection processes. We corrected errors that typists made and inserted errors in correct responses. When asked to report errors, typists took credit for corrected errors and accepted blame for inserted errors, claiming authorship for the appearance of the screen. However, their typing rate showed no evidence of these illusions, slowing down after corrected errors but not after inserted errors. This dissociation suggests two error-detection processes: one sensitive to the appearance of the screen and the other sensitive to keystrokes.